PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN SAMPANG (Studi Empiris Pada SKPD Kabupaten Sampang) - Hanafi Hanafi; M. Cholid Mawardi; Hariri Hariri (Universitas Islam Malang, 2022)
This study aims to determine the effect of human resource competence, utilization of accounting information systems, and control systems on the financial quality of the Sampang district government (Empirical Study on the SKPD of Sampang district). The independent variables in this study are the influence of human resource competency, utilization of accounting information systems, and internal control systems, while the dependent variable is the quality of the Sampang district government's financial reports. This type of research is quantitative research because the data used is numbers and numbers. The source of data in this study is primary data, with the data collection method in the form of a questionnaire. The population in this study is the manager of the work unit or the official of the Regional Work Unit (SKPD) in Sampang Regency. The data collection technique is by giving a set of written statements or questions to the respondents to answer. The questionnaire from this study is a questionnaire that uses a Likert scale to clarify the variables measured in the study. The variables used are a score or value system with a 4-point Likert scale. Based on this method, the number of SKPD used is 45 respondents. The hypotheses were tested using descriptive statistical analysis, instrument testing, normality test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS Version 22. The results showed that the variable of human resource competence had no effect on the quality of financial statements ( 0.713 0.05) and the variable of accounting information system utilization has a significant positive effect on the quality of financial statements (0.014 0.05), while the internal control system variable has a significant positive effect on the quality of financial statements (0.028 0.05).Keywords: Human Resources Competence, Utilization of Accounting Information Systems and Internal Control Systems